Correction: A scoping review of the residual barriers to skilled birth attendance in Ghana: A conceptual framework and a fish bone analysis. - Juliet Abredu; Catherine K Dwumfour; Boo Alipitio; Mawusi Alordey; Veronica Millicent Dzomeku; Sophie Witter (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0002902.].